Quem são os novos agricultores familiares?: um estudo de caso da microrregião de Jales-SP - Souza, Gabriela dos Santos [UNESP] (2013)
Almost all studies confirmed the succession crisis and delineate a negative perspective for the family farm. Many surveys also point out that succession has occurred increasingly later but have not searched to investigate who these recent successors, those farmers who have taken in recent years the management of the family farm. Results of the Censo Agropecuário for 2006 indicate an increase in the number of family farms, it shows that either by inheritance or by creating new family property (rural settlements and / or via the land market) somehow this succession process has occurred. his paper adopts an innovative approach is proposed to investigate who these new farmers. The purpose of this study was therefore to characterize and analyze the strategies of family farmers who assumed the management of the properties in the last ten years to identify the processes of succession that are actually occurring and / or other forms of input such producers in agriculture, microregion of Jales-SP. Were used secondary and primary sources for defining the characteristics of the sample of farmers surveyed and applied a questionnaire to 50 producers of the microregion of Jales with a time period of three to ten years of propriety management. With the results may notice that the new farmer family in the microregion Jales mostly despite having some link with the urban, he has rural origins e acquired his property by purchase by rural work or urban. Was largely positive assessment of these producers in relation to the changes in their lives and / or their incomes after purchase or have assumed the property unattended. Although they assess that one of the sons will be the successor of the property, most of these producers consider that the family farm can‟t have a promising future if government incentives are still scarce. Among those who took the property through inheritance predominated equal share, considered ...